A global history of early modern violence - Charters, Erica; Houllemare, Marie; Wilson, Peter H. (Manchester University Press, 2020)
By expanding the geographical scope of the history of violence and war, this volume challenges both Western and state-centric narratives of the decline of violence and its relationship to modernity. It highlights instead similarities across early modernity in terms of representations, legitimations, applications of, and motivations for violence. It seeks to integrate methodologies of the study of violence into the history of war, thereby extending the historical significance of both fields of research. Thirteen case studies outline the myriad ways in which large-scale violence was understood and used by states and non-state actors throughout the early modern period across Africa, Asia, the Americas, the Atlantic, and Europe, demonstrating that it was far more complex than would be suggested by simple narratives of conquest and resistance. Moreover, key features of imperial violence apply equally to large-scale violence within societies. As the authors argue, violence was a continuum, ranging from small-scale, local actions to full-blown war. The latter was privileged legally and increasingly associated with states during early modernity, but its legitimacy was frequently contested and many of its violent forms, such as raiding and destruction of buildings and crops, could be found in activities not officially classed as war.